Plan de negocio para la creación de la producción de una microempresa productora de decoraciones para el hogar, cantón el Empalme, provincia del Guayas, año 2013 - Perez Cevallos, Bolivar Salomon (2015)
This study on a business plan to undertake in the development of home décor in Canton El Empalme elements is a proposal dedicated to the craft, and the project has raised according to market needs. The investigation primarily a diagnosis of the current situation, formulation of objectives, approach the hypotheses was performed, then the theoretical, conceptual and legal framework for the research was developed by formulating theoretical concepts that were used for the process of elaboration of the thesis. In developing the thesis market research determined that there is an unmet demand relative to existing supply. The technical study analyzed the size, location, infrastructure required to carry out the activities of the company, as well as to the process production of the plant, the financial investment required by the project is detailed in the financial statements, income statement, balance sheet and cash flow is the basis for the financial evaluation and served to determine the net present value, internal rate return and the benefit These issues were relevant to the project that ends with the conclusions and recommendations can be presented in a sustainable project over time or the rated life